On the stability of approximate solutions to set-valued equilibrium problems. (2nd August 2020) - Anh, Lam Quoc; Duoc, Pham Thanh; Tam, Tran Ngoc
Abstract : In this paper, we consider set-valued equilibrium problems in Hausdorff locally convex topological vector spaces. Based on linear scalarization techniques for sets, we study sufficient conditions for the stability of approximate solutions to such problems. Variational inequalities with equilibrium constraints and weak traffic network equilibrium problems are also discussed as applications of the main results.